2022-RA-660-ESGO Characterization of extended treatment benefit from three phase 1 and 3 clinical trials examining patients with folate receptor alpha-positive recurrent ovarian cancer treated with single-agent mirvetuximab soravtansine. (20th October 2022) - Oaknin, Ana; Lorusso, Domenica; Oza, Amit; Colombo, Nicoletta; van Gorp, Toon; O'Malley, David; Banerjee, Susana; Murphy, Conleth; Harter, Philipp; Konecny, Gottfried; Kaminsky, Marie-Christine; Method, Michael; et al.
Abstract : Introduction/Background: Mirvetuximab soravtansine (MIRV) is a first-in-class antibody-drug conjugate comprising a folate receptor alpha (FRα)-binding antibody, cleavable linker, and the maytansinoid payload DM4, a potent tubulin-targeting agent that has demonstrated significant antitumor activity in this difficult-to-treat ovarian cancer population. The objective was to characterize the patients with FRα-positive recurrent ovarian cancer who achieved extended treatment benefit ([ETB]; progression-free survival for >12 months) with MIRV monotherapy. Methodology: Retrospective pooled analysis included patients enrolled across three trials: phase 1 first-in-human, phase 3 FORWARD I, and phase 3 SORAYA. Analysis included patients with low, medium, and high FRα expression by immunohistochemistry. All patients received intravenous MIRV at 6 mg/kg, adjusted ideal body weight, every three weeks until disease progression or unacceptable toxicity. Results: Of the 464 patients included in the analysis, 40 ETB patients were identified: median age 63 years, median of one prior therapy, 52.5% with prior PARPi, and 60% with prior bevacizumab. ETB patients had an overall response rate of 75.0%, with 9 (22.5%) achieving a complete response and 21 (52.5%) achieving a partial response by RECIST v1.1 and demonstrated a median duration of response of 22.1 months (95% CI, 13.8–60.0; interquartile range 13.5–60.0). The most common treatment-related adverse events (TRAEs) (all grade, grade 3+) included blurred vision (60%, 0%), fatigue (50%, 2.5%), nausea (50%, 0%), and keratopathy (40%, 2.5%). Peripheral neuropathy was present in 35% (no grade 3+) and pneumonitis was present in 20% (no grade 3+). TRAEs led to dose delay or reduction in 65% and 47.5% of ETB patients, respectively, and discontinuation in six patients. Conclusion: In a pooled analysis of 464 patients, MIRV monotherapy demonstrated ETB in 10% patients. The safety profile consisted primarily of low-grade gastrointestinal and ocular events and reinforces MIRV's potential to become a new standard of care for FRα-positive ovarian cancer.